In vitro polymerization of flagellin excreted by a short-flagellum Salmonella typhimurium mutant. - Ikeda, T (1984)
The culture medium of a short-flagellum mutant of Salmonella typhimurium contained a large amount of mutant flagellin and a small amount of strong inhibitors of flagellin polymerization. After being freed of the inhibitors, the mutant flagellin could be polymerized in vitro, although under nonphysiological conditions.